Integração de políticas sociais: um estudo de caso sobre o Bolsa Família - Monteiro, Iraneth Rodrigues (2011)
This study proposes to examine the process of integration of the various actions to transfer income under the federal government during the first administration of President Luiz Inacio Lula da Silva, between the years 2003 and 2006, which resulted in the creation of Bolsa Família Program.The proposed analysis seeks to contribute to the knowledge about government and public administration, generating information on the formation of the government agenda of a government committed, programmatically, with the reduction of poverty and social inequality. Regarding the methodological path traversed in the preparation of this thesis, we started with the following key question: Why and how was the process of integration of the Bolsa Família Program? The methodology applied consisted in identifying the reasons for entering this issue on the government agenda of the President ́s Lula first government. To that end, we conducted a case study,to identify which actors participated in the discussion on the unification of income transfer programs and what were the concepts that guided. As a research tool, it was decided by the application of semi-structured interviews with some participants of the Working Group of the Unified Income Transfer Programs. Besides the interviews, other sources were used: the reports and / or minutes of meetings of the Working Group, the Board of Social Policy of the government, the laws of the previous programs, the legislation of the Bolsa Família Program, the speeches made by President-elect Luiz Inacio Lula da Silva from January to October 2003. Through the analysis of all the documentation listed, you can check the government effort to implement changes in income transfer programs. Reports of these meetings were produced by the technical groups, addressing the social policies for reducing inequalities, building the Bolsa Família Program taking into account the importance of the historical legacy of the existing shares. As results, it was found that President Lula, the Board of Social Policy and its group of technical experts were able to seize the window of opportunity for a government that was beginning to develop with strong public policies to fight hunger and poverty. After walking the path of historical reconstruction for the preparation of this manuscript, we attempted to highlight some contributions that aims to provide an incentive for further studies on decision making in the public sphere of government.